Исследование количественного содержания полисахаридов в траве портулака огородного и портулака крупноцветкового - Киниченко, А. А.; Тржецинский, С. Д.; Kinichenko, A. O.; Trzhetsynskyi, S. D.; Кініченко, Анна Олександрівна; Тржецинський, Сергій Дмитрович (My University, 2018)
The results of determination of the quantitative content of alcohol-soluble monosaccharides and polysaccharides fractions (water-soluble polysaccharides, pectin substances and hemicelluloses) in herb of Portulaca oleracea and Portulaca grandifl ora are presented. Both plants are of genus Portulaca L. of the fl ora of Ukraine. The investigation was carried out by using spectrophotometric method. The highest content of the amount of alcohol-soluble monosaccharides and pectin substances was found in herb of Portulaca grandifl ora (6.13% and 1.68%, respectively). According to the quantitative content of the amount of water-soluble polysaccharides, the herb of Portulaca oleracea has dominant position. The highest content of the hemicelluloses amount (10.92%) was determined in the herb of Portulaca oleracea. The obtained data of quantitative content of polysaccharides in herb of Portulaca oleracea and Portulaca grandifl ora can be used in the development of methods of quality control of plant materials and further pharmacological studies.
Investigation of the quantitative content of polysaccharides in herb of Portulaca oleracea and Portulaca grandifl ora
Keywords: Portulaca oleracea; Portulaca grandifl ora; polysaccharides; spectrophotometry